Peningkatan Pemahaman Peserta Didik Terhadap Butir Soal Tes Tertulis - Ryzca Siti Qomariyah; Ika Putri Fadilah; Devi Puspita (CV. ITTC INDONESIA, 2022)
The quality of education can be measured by a test, both honest and descriptive written tests. The test is an action in measuring the success or failure of a teaching. In this group research, a written test was used to determine students' ability to understand matter and its changes. Where is the system for making this problem the first is the preparation and adjustment of the grid with the syllabus and lesson plans that have been set by the class IV teacher. second, preparation of questions that are adapted to the grid. In the observation carried out at SDN Mentor 3, the group found out about the learning model that was applied in class IV, namely the PjBL model with the curriculum used was an independent curriculum, which based on the results of interviews with class IV teachers, science learning in class IV SDN Mentor 3 went well. both and the students are active and have no difficulty in learning science material, especially in the material Forms of Substance and Its Changes. so that the group can find solutions to problems experienced by students.